Long-term effects of COVID-19 on cardiovascular function - Dill, B. (Wittenberg University, 2022)
While majority of the evidence shows acute and longitudinal cardiovascular anomalies exist in a patient population following COVID-19 infection, little is known about subsequent cardiovascular effects in a student-athlete population. With known potential effects to student-athletes pulmonary function, it is reasonable to assume long-term cardiovascular complications exist as well. Therefore, the aim of this study is to determine if longitudinal cardiovascular effects of COVID-19 exist in student-athletes. Twenty-four college-aged student-athletes were split into two groups for comparison based on self-reported COVID status. Twelve subjects reported to have tested positive for COVID-19 10-14 months prior (COV+), while the other twelve participants reported to have never tested positive for COVID-19 (CON). Both groups were sport-matched to ensure that cardiorespiratory fitness was comparable. Direct comparison of both groups was analyzed for VO2, heart rate, and blood pressure via student t-tests with significance set a priori at p<0.05. Age, resting heart rate, resting mean arterial pressure, VO2peak were not different between groups. Additionally, heart rate and mean arterial pressure during exercise corresponding to 85% HRR was not different between groups. Heart rate recovery and mean arterial pressure recovery after exercise was different between groups, with a longer recovery period for the COV+ group compared to the CON group. The mean arterial pressure recovery time is prolonged before returning to resting levels in the representative subject from the COV+ group. Additionally, heart rate was slowed in returning to resting levels in the COV+ group. Interestingly, no differences existed between groups regarding heart rate and mean arterial pressure during exercise.